PERANCANGAN E-CRM DI KANTOR PERTANIAN GARUT: INTEGRASI PEMASARAN, MONITORING, DAN TEKNOLOGI DALAM PELAYANAN MASYARAKAT - Senny Luckyardi; Ratih Hurriyati; Puspo Dewi Dirgantari (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2021)
This study aims to design and analyze e-CRM with a holistic framework at the Garut Agricultural Office. The e-CRM can assist the Garut Agricultural Office and farming communities in the area to overcome various strategic issues and comprehensively reviewing e-CRM. The method used in this study is a qualitative method using interview and observation as the data collection techniques, and Prototyping as the system development method. The results of this study indicate that the designed E-CRM is considered user-friendly and useful for agricultural stakeholders in Garut district. The design of E-CRM at the Garut Agricultural Office can be used as an alternative solution for strategic issues faced by the Garut Regency agricultural sector, namely marketing, monitoring and IT issues to create quality public services.